IMPLEMENTASI ASESMEN PENDIDIKAN DI SDN PESANGGRAHAN 09 PAGI (TANTANGAN DAN PERAN ORANG TUA) - Ngainul Fahmi; Muchammad Ibnu Muzakir; Tasti Septiviani; Yusuf Saepulloh (Al-Wihdah: Jurnal Pendidikan Islam, 2024)
Abstract This study examines the implementation of educational assessment at SDN Pesanggrahan 09 Pagi, Jakarta, focusing on its effectiveness in supporting student learning. The research employs a qualitative approach using observation, interview, and documentation methods. Findings reveal that the school has implemented various types of assessments, including diagnostic assessments at the beginning of the academic year and formative assessments on a regular basis. The school also strives to involve parents and provide training for teachers to enhance the quality of assessment. The study also identifies areas for improvement, such as the need for quantitative data to measure the impact of assessments, detailed information about the types of assessment instruments used, and an evaluation of the effectiveness of coping strategies. As recommendations, the school should improve the quality of assessments, optimally utilize assessment data, strengthen collaboration with parents, and enhance teacher competency in conducting assessments. This research is expected to contribute to efforts to improve the quality of education at SDN Pesanggrahan 09 Pagi. Keywords: Educational Assessment, Student Learning, Parental Collaboration.   Abstrak Kajian ini meneliti implementasi asesmen pendidikan di SDN Pesanggrahan 09 Pagi, Jakarta, dengan fokus pada efektivitasnya dalam mendukung pembelajaran siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi, wawancara, dan dokumentasi. Hasil kajian menunjukkan bahwa sekolah telah menerapkan berbagai jenis asesmen, termasuk asesmen diagnostik di awal tahun ajaran dan asesmen formatif secara berkala. Sekolah juga berupaya melibatkan orang tua dan memberikan pelatihan kepada guru untuk meningkatkan kualitas asesmen. Kajian ini juga mengungkap beberapa area yang perlu ditingkatkan, seperti kebutuhan data kuantitatif untuk mengukur dampak asesmen, rincian jenis-jenis instrumen asesmen yang digunakan, dan evaluasi efektivitas strategi penanganannya. Sebagai rekomendasi, sekolah perlu meningkatkan kualitas asesmen, memanfaatkan data asesmen secara optimal, memperkuat kolaborasi dengan orang tua, dan meningkatkan kompetensi guru dalam melaksanakan asesmen. Penelitian ini diharapkan dapat memberikan sumbangan bagi upaya peningkatan kualitas pendidikan di SDN Pesanggrahan 09 Pagi. Kata kunci: Asesmen Pendidikan, Pembelajaran Siswa, Kolaborasi Orang Tua.